Boron-containing carbon material, conductive composition, and conductive film

JP7632004B2Active Publication Date: 2025-02-19TOYO INK MFG CO LTD
View PDF -1 Cites 0 Cited by

Patent Information

Application Number
JP2021063114
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Priority Date
2020-04-03
Filing Date
2021-04-01
Publication Date
2025-02-19
Estimated Expiration
2041-04-01

Smart Images

  • Figure 0007632004000004
    Figure 0007632004000004
  • Figure 0007632004000001
    Figure 0007632004000001
  • Figure 0007632004000002
    Figure 0007632004000002
Patent Text Reader

Abstract

To provide an excellent conductive material by realizing a boron-containing carbon material excellent in conductivity.SOLUTION: The problem is solved by a boron-containing carbon material which is doped with a boron element so as to replace at least a part of the carbon element in its carbon skeleton and in which an intensity ratio [G / D] of a G band to a D band in laser Raman spectrum is 1.0 or more and a ratio of a surface substitution type boron element to all the elements on a surface of the boron-containing carbon material, as measured by X-ray photoelectron spectroscopy (XPS), is 0.0001 or more.SELECTED DRAWING: Figure 1
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a boron-containing carbon material, a conductive composition, and a conductive film. [Background technology]

[0002] In recent years, electronics has developed remarkably, and there is a demand for conductive materials used in various electronic devices to be smaller, lighter, and less expensive, while also providing longer life in a variety of operating environments. For example, when producing circuit board wiring for electronic devices or wiring for connecting electronic devices, a conductive composition with excellent conductivity is required. However, typical conductive compositions that use metal fillers such as silver or copper have significant issues in terms of cost and durability, which have yet to be resolved. On the other hand, various conductive compositions using conductive carbon materials without using metals have been investigated. However, due to insufficient conductivity, their use has been limited to semi-conductive applications such as antistatic applications.

[0003] As conductive carbon materials, highly conductive carbons such as graphite and carbon nanotubes have been considered. The volume resistivity of these highly conductive carbons is 10 -2 It has been reported that the electrical conductivity is less than Ω·cm, and that the electrical conductivity issue can be improved compared to conventional methods (see Patent Documents 1 and 2). However, the volume resistivity of these carbon materials is incomparably higher than that of metal fillers, and it is difficult to say that conductive carbon alone exhibits sufficient properties for conductive applications.

[0004] On the other hand, research has been conducted into highly crystalline carbon materials with the aim of solving the problem of the electrical conductivity of carbon materials. For example, in relation to a method for producing carbon nanotubes, it has been reported that the flow rate and concentration of the raw material gas are improved to improve the crystallinity (see Patent Document 3), and that a structure is formed in which graphene on the surface of carbon fibers is bonded together by the catalytic action of liquid Ga (see Patent Document 4). However, the improvement in electrical conductivity is still insufficient, and there is a demand for the development of carbon materials with even higher electrical conductivity. [Prior art documents] [Patent documents]

[0005] [Patent Document 1] Japanese Patent Application Publication No. 3-7740 [Patent Document 2] JP 2008-293821 A [Patent Document 3] JP 2010-006663 A [Patent Document 4] JP 2009-179915 A Summary of the Invention [Problem to be solved by the invention]

[0006] In view of the above problems, an object of the present invention is to provide a boron-containing carbon material having excellent electrical conductivity, thereby providing an excellent electrically conductive material. [Means for solving the problem]

[0007] The present inventors have conducted extensive research to solve the above-mentioned problems and have arrived at the present invention. That is, the present invention relates to a boron-containing carbon material doped with boron element so as to substitute at least a portion of the carbon element in the carbon skeleton, the boron-containing carbon material having an intensity ratio [G / D] of G band to D band in a laser Raman spectrum of 1.0 or more, and a ratio of surface-substitutional boron element to all elements on the surface of the boron-containing carbon material of 0.0001 or more as measured by X-ray photoelectron spectroscopy (XPS).

[0008] The present invention also relates to the above boron-containing carbon material, which contains at least one material selected from the group consisting of graphite-based carbon materials, graphene-based carbon materials, and carbon nanotube-based carbon materials.

[0009] The present invention also relates to the above boron-containing carbon material, wherein an intensity ratio of G band to D band [G / D] is 1.25 to 5.0.

[0010] The present invention also relates to the above boron-containing carbon material, wherein the ratio of surface-substitutional boron element is 0.0004 or more.

[0011] The present invention also relates to the above boron-containing carbon material, which has a crystallite size (La) of 28 to 80 nm.

[0012] The present invention also relates to a conductive composition containing the above boron-containing carbon material and at least one of a binder resin or a solvent.

[0013] The present invention also relates to the conductive composition, further comprising a conductive assistant.

[0014] The present invention also relates to the conductive composition, wherein the proportion of the boron-containing carbon material in the total solid content of the conductive composition is in the range of 50 to 60 mass %, and the proportion of the conductive assistant is in the range of 10 to 18 mass %.

[0015] The present invention also relates to a conductive film formed from the conductive composition. Effect of the Invention

[0016] According to the present invention, it is possible to provide a boron-containing carbon material having excellent electrical conductivity. [Brief description of the drawings]

[0017] [Figure 1] FIG. 1 is a diagram showing an example of peaks and peak separation in a B1s spectrum in XPS. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0018] The boron-containing carbon material of the present invention is a boron-containing carbon material doped with boron element so as to substitute at least a part of the carbon element in the carbon skeleton, and is characterized in that the intensity ratio [G / D] of the G band to the D band in a laser Raman spectrum is 1.0 or more, and the ratio of surface-substitutional boron element to all elements on the surface of the boron-containing carbon material, as measured by X-ray photoelectron spectroscopy (XPS), is 0.0001 or more. By satisfying all of the above, it is possible to obtain a carbon material with high crystallinity and low defects, doped with boron in an appropriate boron bond state, and exhibit excellent electrical conductivity. Furthermore, the composition containing the carbon material has excellent electrical conductivity and can be used for battery electrodes, current collectors, batteries, wiring for electronic devices, etc. The present invention will be described in detail below. In the present specification, the term "boron-containing carbon material" may be abbreviated to "carbon material".

[0019] <Boron-containing carbon materials> In the present invention, the boron-containing carbon material doped with boron to substitute at least a part of the carbon elements in the carbon skeleton is a carbon material having a basic skeleton of a hexagonal carbon mesh plane in which carbon atoms are covalently bonded in a hexagonal mesh pattern to form a mesh plane, having physical and chemical interactions (bonds) between the structural units, and doped with boron to substitute at least a part of the carbon elements. The boron-containing carbon material of the present invention may contain hetero elements such as nitrogen and phosphorus, or base metal elements, depending on the case.

[0020] Boron-containing carbon materials are characterized by the D band (1330-1370 cm) in the laser Raman spectrum with an excitation laser wavelength of 532 nm. -1 ) and G band (1560~1620cm -1It is important that the [G / D] ratio, which is the ratio of peak intensities (IG / ID) of the two peaks, is 1.0 or more. When the [G / D] ratio is 1.0 or more, there are few defects and crystal interfaces on the carbon surface, and the electron conduction is excellent. The [G / D] ratio is preferably 1.25 or more, more preferably 1.7 or more, even more preferably 2.0 or more, and particularly preferably 2.3 or more. The [G / D] ratio is preferably 7.0 or less, more preferably 5.0 or less.

[0021] In addition, the [G / D] ratio of the boron-containing carbon material is preferably in the range of 1.7 to 5.0, more preferably 2.0 to 5.0. When the ratio is in the above range, not only is the conductivity good when preparing a conductive composition, but the wettability to a solvent or a binder resin is increased, and the hardness tends to increase. This improves the durability against external forces such as impact, and improves the dispersion stability and film strength.

[0022] The form of the boron element on the surface of the boron-containing carbon material is not particularly limited, but examples include substitutional boron element (BC3 type) in which boron element substitutes for carbon element position in the carbon skeleton, boron carbide type and boron cluster type boron element (B4C type, Bc type), boron element in a completely or partially oxidized state of boron oxide type (BC2O type, BCO2 type, B2O3 type), etc.

[0023] It is important that the ratio of surface-substitutional boron element to all elements on the surface of the boron-containing carbon material measured by X-ray photoelectron spectroscopy (XPS) is 0.0001 or more. This improves the carrier density by doping with boron element. The ratio of surface-substitutional boron element is expressed as B×BR, where B is the ratio of the spectral area of ​​all boron element to the spectral area of ​​all elements on the carbon material surface measured by XPS, and BR is the ratio of the peak area of ​​substitutional boron element to the spectral area of ​​all boron element on the carbon material surface obtained from the B1s spectrum of XPS. It is more preferably 0.0002 or more, and even more preferably 0.0004 or more.

[0024] The preferred range of the ratio of surface-substituted boron element in the boron-containing carbon material is 0.0001 to 0.01, more preferably 0.0004 to 0.005. When the ratio is within the above range, not only is the conductivity good when preparing a conductive composition, but the wettability to solvents and binder resins is improved, and the hardness tends to increase. This improves the durability against external forces such as impacts, and improves the dispersion stability and film strength.

[0025] The B1s spectrum of boron obtained by XPS measurement appears in the binding energy range of the B1s electron of boron element (around 185 to 197 eV), and is known to be roughly divided into four components. The binding energy values ​​(peak tops) of each component are 186 to 187 eV for boron clusters, 187 to 188 eV for boron carbide, 188 to 189.3 eV for boron doped to replace carbon elements with a hexagonal mesh surface as the basic skeleton (BC3), 189.5 to 190.5 eV for various boron oxides BC2O, 191.5 to 192 eV for BCO2, and 192.5 to 193 eV for B2O3. When these peaks overlap, the ratio can be determined by fitting each component as a Gaussian function, optimizing the peak intensity, peak position, and full width at half maximum as parameters, and separating the peaks. Therefore, the state of boron on the surface of the boron-doped carbon material can be analyzed by performing peak separation of B1s.

[0026] The electrical conductivity of the boron-containing carbon material is expressed by the following formula. σ=μ×n×e (Equation 1) μ: mobility, n: carrier density, e: elementary charge (constant) From the above formula (1), it is necessary to improve the mobility and / or carrier density in order to improve the electrical conductivity. The main aim of doping carbon materials with boron is to improve the carrier density by introducing holes. On the other hand, doping carbon materials with boron has a significant effect on the crystal structure and electronic state of carbon, and can induce disorder in the crystal structure of carbon, which can reduce the mobility. Therefore, it is important to dope boron in an appropriate boron-bonded state and maintain a high surface crystal state (G / D ratio) in order to increase the carrier density while suppressing the decrease in mobility and to achieve high electrical conductivity.

[0027] The boron-containing carbon material is not particularly limited, and examples thereof include graphite-based carbon materials, carbon nanotube-based carbon materials, graphene-based carbon materials, and carbon black-based carbon materials. Since the boron-containing carbon material tends to have high crystallinity such as a [G / D] ratio, it is preferable to use at least one selected from the group consisting of graphite-based carbon materials, graphene-based carbon materials, and carbon nanotube-based carbon materials.

[0028] The boron-containing carbon material of the present invention is preferably highly crystalline and has large particles because this is advantageous for electronic conductivity. The thickness of the boron-containing carbon material is preferably greater than 50 nm, more preferably greater than 100 nm, and even more preferably greater than 250 nm. The thickness of the particles of the boron-containing carbon material can be determined by, for example, using an electron microscope or the like and using the average value of the thicknesses of particles randomly sampled.

[0029] The crystallite size (La) in the a-axis direction of the boron-containing carbon material is preferably 28 to 80 nm, more preferably 30 to 70 nm, and further preferably 35 to 65 nm. When the crystallite size (La) is in the range of 28 to 80 nm, the electrical conductivity and dispersibility of the boron-containing carbon material are improved, and the electrical conductivity of the electrically conductive composition is improved. The crystallite size (La) can be calculated by performing X-ray diffraction (XRD) measurement. In the XRD measurement, the crystallite size (La) is calculated from the peak position and half-width of the (110) plane diffraction appearing at a diffraction angle (2θ) of about 77.0 to 78.5° in the XRD pattern of the boron-containing carbon material obtained using CuKα radiation as an X-ray source. The calculation method can be, for example, based on the Gakushin method.

[0030] <Method for producing boron-containing carbon material> A preferred method for producing the boron-containing carbon material of the present invention is a method in which a carbon source that has been carbonized in advance is doped with boron. The term "carbonization" used here refers to a phenomenon similar to "crystallization" or "graphitization." For example, in a method of obtaining boron-doped carbon by doping boron while carbonizing a non-carbonized carbon source and a boron source, or in a method of using a carbon source that has been pre-calcined, crystallization or graphitization may be insufficient. For this reason, a method of performing a boron doping reaction after carbonization, such as doping a carbon source that has been pre-carbonized with boron, is preferable to a method of doping boron while carbonizing, because it allows the production of a carbon material with a favorable boron distribution state. That is, in order to obtain the boron-containing carbon material of the present invention that can achieve both excellent electrical conductivity, dispersibility, and durability, the selection of the carbon source and the mixed state of the carbon source and the boron source when the boron doping reaction occurs are also important.

[0031] The method for producing the boron-containing carbon material of the present invention is not particularly limited, but is preferably a method including a step of mixing a carbonaceous raw material with a compound containing boron, and a step of heat-treating the mixture at a high temperature of 1000° C. or more.

[0032] The raw material composition ratio of the carbon-based raw material and the boron-containing compound for producing a boron-containing carbon material is not particularly limited, but the ratio of the boron-containing compound to 100 parts by mass of the carbon-based raw material is preferably 0.01 to 300 parts by mass, and more preferably 0.1 to 100 parts by mass.

[0033] The method for mixing the carbonaceous raw material and the boron-containing compound is not particularly limited, and examples thereof include dry mixing and wet mixing. As a mixing device, the following dry mixing device or wet mixing device can be used.

[0034] Examples of dry mixing devices include roll mills such as two-roll and three-roll devices, high-speed agitators such as Henschel mixers and super mixers, fluid energy pulverizers such as Micronizers and jet mills, attritors, particle composite devices manufactured by Hosokawa Micron Corporation such as "Nanocure," "Nobilta," and "Mechanofusion," and powder surface modification devices manufactured by Nara Machinery Manufacturing Co., Ltd. such as "Hybridization System," "Mechano Micros," and "Miraro." In addition, when using a dry mixer, two or more raw materials may be directly mixed in powder form, but in order to prepare a more uniform mixture, one or more raw materials may be dissolved or dispersed in a small amount of solvent beforehand and then mixed. In order to further increase the processing efficiency, heating may be used.

[0035] Examples of wet mixing devices include mixers such as Disper, Homomixer, or Planetary Mixer, homogenizers such as M-Technique's "Clearmix" or PRIMIX's "Filmix", Red Devil's paint conditioner, ball mill, sand mills such as Shinmaru Enterprises' "Dynomill", attritor, or Coball Mill, media-type dispersers, Genus' "Genus PY", Sugino Machine's "Starburst", Nanomizer's "Nanomizer", wet jet mills, M-Technique's "Clear SS-5", or Nara Machinery's "Micros", media-less dispersers, roll mills, kneaders, ultrasonic dispersers, etc., but are not limited thereto. In addition, it may be preferable to use a wet mixing device that has been treated to prevent metal from entering the device. For example, when using a media-type disperser, it is preferable to use a method in which a disperser with an agitator and a vessel made of ceramic or resin is used, or a disperser in which the surface of a metal agitator and a vessel is treated with tungsten carbide spraying, resin coating, etc. As the media, it is preferable to use ceramic beads such as glass beads, zirconia beads, or alumina beads. Also, when using a roll mill, it is preferable to use a ceramic roll. The dispersion device may be used alone or in combination of two or more types.

[0036] In addition, when the raw materials are not uniformly dissolved or dispersed, in order to improve the wettability and dispersibility of each raw material in the solvent, multiple solvents may be used in combination as necessary, or a dispersant may be added to disperse or mix the raw materials. In particular, since it is difficult to uniformly mix a boron source with a carbonized (graphitized) carbon source, the mixing (contact) state of the carbon source and the boron source when the boron doping reaction occurs is important, and it is preferable to treat the carbon source and the boron source uniformly.

[0037] The dispersant functions effectively as a dispersant for each raw material and can alleviate the aggregation thereof. The dispersant is not particularly limited as long as it has the effect of alleviating aggregation, and any dispersant known in the art can be used, such as a resin-type dispersant, a surfactant, or a pigment derivative.

[0038] Examples of the resin-type dispersant include polyvinyl resins, polyurethane resins, polyester resins, polyether resins, cellulose resins such as carboxymethyl cellulose, formalin condensates, silicone resins, and composite polymers thereof. Preferred are polyvinylpyrrolidone, polyvinyl alcohol, polystyrene sulfonic acid, polyacrylic acid, carboxymethyl cellulose, etc. Two or more of these resin-type dispersants may be used in combination.

[0039] In the step of heat-treating the mixture, the heating temperature varies depending on the types and amounts of the carbonaceous raw materials and the boron-containing compound used as raw materials, but is preferably 1000 to 3200° C., and more preferably 1800 to 3000° C. The heating time is not particularly limited, but is usually preferably 30 minutes to 10 hours. The heat treatment step is preferably carried out in an inert gas atmosphere such as nitrogen or argon, or in a vacuum atmosphere to prevent oxidation of the raw material. The heat treatment step may be carried out not only in one stage under a constant atmosphere and temperature, but also in multiple stages by changing the atmosphere and temperature each time.

[0040] [Carbon-based raw materials] The carbonaceous raw material for producing the boron-containing carbon material of the present invention is preferably an inorganic carbonaceous raw material. Examples of the inorganic carbonaceous raw material include carbon black (furnace black, acetylene black, ketjen black, medium thermal carbon black), activated carbon, graphite, carbon nanotubes, carbon nanofibers, carbon nanohorns, graphene, graphene nanoplatelets, nanoporous carbon, carbon fibers, and charcoal. The above carbonaceous raw materials come in a variety of sizes of hexagonal carbon mesh planes and layered structures, and differ in various physical properties such as crystallinity, particle size, shape, BET specific surface area, pore volume, pore size, bulk density, DBP oil absorption, surface acid-basicity, surface hydrophilicity, and electrical conductivity, as well as cost. Therefore, the optimal material can be selected depending on the application and required performance.

[0041] Examples of commercially available carbonaceous raw materials include, but are not limited to, the following: Examples of commercially available graphite include CMX, UP-5, UP-10, UP-20, UP-35N, CSSP, CSPE, CSP, CP, CB-150, CB-100, ACP, ACP-1000, ACB-50, ACB-100, ACB-150, SP-10, SP-20, J-SP, SP-270, HOP, GR-60, LEP, F#1, F#2, F#3, CGC-20, and CGC-50, CGB-20, CGB-50, PAG-60, PAG-80, PAG-120, PAG-5, HAG-10W, HAG-150, Ito Graphite Industries' EC1500, EC1000, EC500, EC300, EC100, EC50, Chuetsu Graphite's CX-3000, FBF, BF, CBR, SSC-3000, SSC-600, SSC-3, SSC, CX-600, CPF-8 , CPF-3, CPB-6S, CPB, 96E, 96L, 96L-3, 90L-3, CPC, S-87, K-3, CF-80, CF-48, CF-32, CP-150, CP-100, CP, H F-80, HF-48, HF-32, SC-120, SC-80, SC-60, SC-32, RA-3000, RA-15, RA-44, GX-600, G-6S, G-3, G-150, G-10 Examples of such carbon blacks include SGP-100, SGP-50, SGP-25, SGP-15, SGP-5, SGP-1, SGO-100, SGO-50, SGO-25, SGO-15, SGO-5, SGO-1, SGX-100, SGX-50, SGX-25, SGX-15, SGX-5, and SGX-1 manufactured by SEC Carbon Co., Ltd., and 10099M and PB-99 manufactured by Nishimura Graphite Co., Ltd.

[0042] Examples of commercially available carbon black include Ketjen Black EC-300J, EC-600JD, and Lionite EC-200L manufactured by Lion Specialty Chemicals; Furnace Black #2350, #2600, #3050B, #3030B, #3230B, and #3400B manufactured by Mitsubishi Chemical Corporation; and Denka Black HS-100 and FX-35 manufactured by Denka Company. Examples of commercially available carbon nanotubes include VGCF-H and VGCF-X manufactured by Showa Denko K.K., carbon nanotubes manufactured by Meijo Nano Carbon K.K., NTP3003, NTP3021, NTP3121, NTP8012, NTP8022, NTP9012, NTP9112 manufactured by NTP, and TUBALL manufactured by OCSiAl. Examples of commercially available graphene-based carbon include graphene nanoplatelets xGnP-C-300, xGnP-C-500, xGnP-C-750, xGnP-M-5, xGnP-M-15, xGnP-M-25, xGnP-H-5, xGnP-H-15, and xGnP-H-25 manufactured by XG Sciences. Among these, graphite is preferred as a commercially available carbonaceous raw material from the viewpoints of electrical conductivity and cost.

[0043] As the carbonaceous raw material for producing the boron-containing carbon material of the present invention, an organic carbonaceous raw material that becomes carbon particles after heat treatment can be used. Examples of such organic carbonaceous raw materials include phenolic resins, polyimide resins, polyamide resins, polyamideimide resins, polyacrylonitrile resins, polyaniline resins, phenol formaldehyde resins, polyimidazole resins, polypyrrole resins, polybenzimidazole resins, melamine resins, pitch, coke, lignite, polycarbodiimide, biomass, protein, humic acid, and derivatives thereof. Among them, it is preferable to use coke and pitch, which are also used as raw materials for graphite.

[0044] [Boron-containing compounds] Next, a compound containing boron used in the production of the boron-containing carbon material will be described. The compound containing boron is not particularly limited, but for example, B4C(B 12 C3), B 12 Boron carbides such as C2(B6C); BC2O, BCO2, B2O2, B2O3, B4O3, Boron oxides such as B4O5; boron nitrides such as BN; AlB2, CoB, FeB, MgB2, Examples of the boron-containing organic compounds include metal borides such as NiB and TiB2; boron oxoacids such as orthoboric acid, metaboric acid, and tetraboric acid; boranes such as monoborane, diborane, and decaborane; and boron-containing organic compounds such as borate esters, substituted boranes, and boronic acids. Examples of the borate esters include trimethyl borate and triethyl borate. Examples of the substituted boranes include triethylborane and triphenylborane. Examples of the boronic acids include phenylboronic acid and phenylboronic acid esters.

[0045] <Conductive composition> The conductive composition of the present invention contains the above-mentioned boron-containing carbon material and at least one of a binder resin and a solvent. The conductive composition may contain two or more different carbon materials in combination, and may contain a conductive assistant as necessary.

[0046] <Binder resin> The binder resin is not particularly limited, and may include, for example, at least one type selected from the group consisting of polyurethane resins, polyamide resins, acrylonitrile resins, acrylic resins, butadiene resins, polyvinyl resins, polyvinyl butyral resins, polyolefin resins, polyester resins, polystyrene resins, EVA resins, polyvinylidene fluoride resins, polytetrafluoroethylene resins, silicone resins, polyether resins, cellulose resins such as carboxymethyl cellulose, and the like. The binder resins may be used alone or in combination of two or more kinds.

[0047] From the viewpoints of volume resistivity, adhesion to the substrate, and durability, the binder resin preferably contains at least one selected from the group consisting of polyurethane-based, polyamide-based, and polyester-based resins, and more preferably contains a polyurethane-based resin. The binder resin is preferably one that moderately softens or flows when the conductive composition is printed or coated on the substrate and then pressed or hot-pressed (hereinafter referred to as (hot) pressing). By using such a resin, the conductive composition flows in the thickness direction while maintaining the planar pattern shape of the coating film, the voids in the film are reduced, and the contact points between the carbon materials are increased, resulting in a conductive film with low volume resistivity.

[0048] [Polyurethane resin] The method for synthesizing the polyurethane resin is not particularly limited, and examples thereof include a method of reacting a polyol compound (a) with a diisocyanate (b), a method of reacting the polyol compound (a), the diisocyanate (b), and a diol compound (c) having a carboxyl group to obtain a urethane prepolymer (d) having an isocyanate group, a method of further reacting the urethane prepolymer (d) with a polyamino compound (e), and a method of reacting a reaction terminator with any of the above three methods, if necessary.

[0049] As the polyol compound (a), various polyether polyols, polyester polyols, polycarbonate polyols, polybutadiene glycols, or mixtures thereof, which are known as polyol components constituting polyurethane resins, can be used.

[0050] Examples of polyether polyols include polymers or copolymers of ethylene oxide, propylene oxide, tetrahydrofuran, and the like. Examples of polyester polyols include saturated and unsaturated low molecular weight diols such as ethylene glycol, 1,2-propanediol, 1,3-propanediol, 1,3-butanediol, 1,4-butanediol, neopentyl glycol, pentanediol, 3-methyl-1,5-pentanediol, hexanediol, octanediol, 1,4-butylenediol, diethylene glycol, triethylene glycol, dipropylene glycol, and dimer diol, as well as n-butyl glycidyl ether, 2-ethyl glycidyl ether, and the like. Examples of the polyester polyols include polyester polyols obtained by dehydration condensation of alkyl glycidyl ethers such as hexyl glycidyl ethers, monocarboxylic acid glycidyl esters such as versatic acid glycidyl ester, and dicarboxylic acids such as adipic acid, phthalic acid, isophthalic acid, terephthalic acid, maleic acid, fumaric acid, succinic acid, oxalic acid, malonic acid, glutaric acid, pimelic acid, suberic acid, azelaic acid, and sebacic acid, or anhydrides thereof, and polyester polyols obtained by ring-opening polymerization of cyclic ester compounds. Examples of polycarbonate polyols that can be used include (1) a reaction product of a diol or bisphenol with a carbonate ester, and (2) a reaction product of a diol or bisphenol with phosgene in the presence of an alkali. Examples of carbonate esters include dimethyl carbonate, diethyl carbonate, diphenyl carbonate, ethylene carbonate, and propylene carbonate. Examples of diols include ethylene glycol, propylene glycol, dipropylene glycol, diethylene glycol, triethylene glycol, butylene glycol, 3-methyl-1,5-pentanediol, 2-methyl-1,8-octanediol, 3,3'-dimethylolheptane, polyoxyethylene glycol, polyoxypropylene glycol, propanediol, 1,3-butanediol, 1,4-butanediol, 1,5-pentanediol, 1,6-hexanediol, and 1,9-nonanediol. Examples of bisphenols include bisphenol A, bisphenol F, and bisphenols obtained by adding alkylene oxides such as ethylene oxide and propylene oxide to bisphenols.

[0051] The number average molecular weight (Mn) of the polyol compound is appropriately determined taking into consideration the solubility of the polyurethane resin when producing the conductive composition, the durability of the conductive film formed, and the adhesive strength to the substrate, and is usually preferably in the range of 580 to 8,000, and more preferably in the range of 1,000 to 5,000. The polyol compounds may be used alone or in combination of two or more. Furthermore, a part of the polyol compounds may be replaced with low molecular weight diols, for example, various low molecular weight diols used in the production of the polyol compounds, within the range in which the performance of the polyurethane resin is not lost.

[0052] As the diisocyanate compound (b), an aromatic diisocyanate, an aliphatic diisocyanate, an alicyclic diisocyanate, or a mixture thereof can be used. An alicyclic diisocyanate is preferable, and isophorone diisocyanate is more preferable. As the aromatic diisocyanate, 1,5-naphthylene diisocyanate, 4,4'-diphenylmethane diisocyanate, 4,4'-diphenyldimethylmethane diisocyanate, 4,4'-benzyl isocyanate, dialkyldiphenylmethane diisocyanate, tetraalkyldiphenylmethane diisocyanate, 1,3-phenylene diisocyanate, 1,4-phenylene diisocyanate, tolylene diisocyanate, xylylene diisocyanate, etc. can be mentioned.

[0053] Examples of the aliphatic diisocyanate include butane-1,4-diisocyanate, hexamethylene diisocyanate, 2,2,4-trimethylhexamethylene diisocyanate, and lysine diisocyanate. Examples of the alicyclic diisocyanate include cyclohexane-1,4-diisocyanate, isophorone diisocyanate, norbornane diisocyanate methyl, bis(4-isocyanate cyclohexyl)methane, 1,3-bis(isocyanate methyl)cyclohexane, and methylcyclohexane diisocyanate.

[0054] Examples of the diol compound (c) having a carboxyl group include dimethylolalkanoic acids such as dimethylolacetic acid, dimethylolpropionic acid, dimethylolbutanoic acid, and dimethylolpentanoic acid, dihydroxysuccinic acid, and dihydroxybenzoic acid. Dimethylolpropionic acid and dimethylolbutanoic acid are particularly preferred from the standpoint of reactivity and solubility. The conditions for reacting a polyol compound (a), a diisocyanate (b), and a diol compound (c) having a carboxyl group to obtain a urethane prepolymer (d) having an isocyanate group are not particularly limited except that the isocyanate group is in excess, but the equivalent ratio of isocyanate group / hydroxyl group is preferably within the range of 1.05 / 1 to 3 / 1. More preferably, it is 1.2 / 1 to 2 / 1. The reaction is usually carried out at a temperature between room temperature and 150°C, and is preferably carried out at a temperature between 60 and 120°C from the viewpoints of production time and control of side reactions.

[0055] The polyamino compound (e) acts as a chain extender, and examples of the polyamino compound that can be used include ethylenediamine, propylenediamine, hexamethylenediamine, diethylenetriamine, triethylenetetramine, isophoronediamine, dicyclohexylmethane-4,4'-diamine, and norbornanediamine, as well as amines having a hydroxyl group such as 2-(2-aminoethylamino)ethanol, 2-hydroxyethylethylenediamine, 2-hydroxyethylpropylenediamine, di-2-hydroxyethylethylenediamine, and di-2-hydroxypropylethylenediamine. Of these, isophoronediamine is preferably used.

[0056] When synthesizing a polyurethane resin by reacting a urethane prepolymer (d) having an isocyanate group with a polyamino compound (e), a reaction terminator can be used in combination to adjust the molecular weight of the resulting polyurethane resin. Examples of reaction terminators that can be used include dialkylamines such as di-n-butylamine, dialkanolamines such as diethanolamine, and alcohols such as ethanol and isopropyl alcohol.

[0057] The conditions for reacting the urethane prepolymer (d) having an isocyanate group with the polyamino compound (e) and, if necessary, with a reaction terminator are not particularly limited, but when the free isocyanate groups at both ends of the urethane prepolymer are taken as 1 equivalent, the total equivalent of the amino groups in the polyamino compound (e) and the reaction terminator is preferably within a range of 0.5 to 1.3, more preferably within a range of 0.8 to 0.995. The weight average molecular weight of the polyurethane resin is preferably in the range of 5,000 to 200,000 from the viewpoints of coatability and handleability.

[0058] [Polyamide resin] Polyamide resin is a general term for polymers having amide bonds obtained by various reactions such as polycondensation of dibasic acids and diamines, polycondensation of aminocarboxylic acids, or ring-opening polymerization of lactams. It includes various modified polyamides and those produced from partially hydrogenated reaction products. Polymers partially copolymerized with other monomers, or mixtures of other substances such as various additives can be used. The polyamide resin is not particularly limited, but a dimer acid modified polyamide resin obtained by condensation polymerization of a dibasic acid mainly composed of a dimer acid and a polyamine is preferable. As the dimer acid for producing the dimer acid modified polyamide resin, a dimer acid obtained by polymerizing a natural monobasic unsaturated fatty acid contained in tall oil fatty acid, soybean oil fatty acid, etc. is widely used industrially, but in principle, various dicarboxylic acids such as saturated aliphatic, unsaturated aliphatic, alicyclic, or aromatic may be used. Commercially available products of the dimer acid include Haridimer 200, 300 (manufactured by Harima Chemicals), Versadigm 228, 216, Empol 1018, 1019, 1061, 1062 (manufactured by Cognis), etc. Furthermore, hydrogenated dimer acid can also be used, and commercially available products of hydrogenated dimer acid include Pripol 1009 (manufactured by Croda Japan Co., Ltd.) and Empol 1008 (manufactured by Cognis). In addition to the above dimer acids, various dicarboxylic acids can be used as dibasic acids to obtain polyamide resins with suitable flexibility. Specific examples of dicarboxylic acids include oxalic acid, malonic acid, succinic acid (anhydride), maleic acid (anhydride), glutaric acid, adipic acid, vimelic acid, suberic acid, azelaic acid, sebacic acid, terephthalic acid, isophthalic acid, phthalic acid, naphthalenedicarboxylic acid, 1,3- or 1,4-cyclohexanedicarboxylic acid, 1,18-octadecanedicarboxylic acid, and 1,16-hexadecanedicarboxylic acid.

[0059] Furthermore, a dibasic acid having a phenolic hydroxyl group can also be used. By using a dibasic acid having a phenolic hydroxyl group, the phenolic hydroxyl group can be introduced into the side chain of the polyamide resin, and can be used in the reaction with the curing agent. Examples of dibasic acids having a phenolic hydroxyl group include hydroxyisophthalic acids such as 2-hydroxyisophthalic acid, 4-hydroxyisophthalic acid, and 5-hydroxyisophthalic acid; dihydroxyisophthalic acids such as 2,5-dihydroxyisophthalic acid, 2,4-dihydroxyisophthalic acid, and 4,6-dihydroxyisophthalic acid; dihydroxyterephthalic acids such as 2-hydroxyterephthalic acid, 2,3-dihydroxyterephthalic acid, and 2,6-dihydroxyterephthalic acid; hydroxyphthalic acids such as 4-hydroxyphthalic acid and 3-hydroxyphthalic acid; and dihydroxyphthalic acids such as 3,4-dihydroxyphthalic acid, 3,5-dihydroxyphthalic acid, 4,5-dihydroxyphthalic acid, and 3,6-dihydroxyphthalic acid. Further examples include acid anhydrides and ester derivatives such as polybasic acid methyl esters. Among these, 5-hydroxyisophthalic acid is preferred from the standpoints of copolymerizability, availability, and the like.

[0060] Furthermore, in order to obtain a polyamide resin with suitable fluidity when heated, various monocarboxylic acids are used as necessary, such as propionic acid, acetic acid, caprylic acid (octanoic acid), stearic acid, and oleic acid. The polyamines used as reactants in producing the dimer acid modified polyamide resin include, for example, various aliphatic, alicyclic and aromatic diamines, triamines and polyamines. Specific examples of the diamine include ethylenediamine, propanediamine, butanediamine, triethylenediamine, tetraethylenediamine, hexamethylenediamine, p- or m-xylenediamine, 4,4'-methylenebis(cyclohexylamine), 2,2-bis-(4-cyclohexylamine), polyglycoldiamine, isophoronediamine, 1,2-, 1,3- or 1,4-cyclohexanediamine, 1,4-bis-(2'-aminoethyl)benzene, N-ethylaminopiperazine, and piperazine. In addition, examples of triamines include diethylenetriamine, and examples of polyamines include triethylenetetramine, tetraethylenepentamine, pentaethylenehexamine, etc. Furthermore, dimer diamines obtained by converting a dimerized aliphatic nitrile group and reducing it with hydrogen can also be used.

[0061] Furthermore, examples of polyamine compounds include compounds in which the carboxyl group of a polybasic acid compound having a cyclic or acyclic hydrocarbon group having 20 to 48 carbon atoms is converted to an amino group. Examples of commercially available products include "Priamine 1071", "Priamine 1073", "Priamine 1074", and "Priamine 1075" manufactured by Croda Japan Co., Ltd., and "Versamine 551" manufactured by Cognis Japan Co., Ltd. The diamine may be used in combination with an alkanolamine. Examples of the alkanolamine include ethanolamine, propanolamine, diethanolamine, butanolamine, 2-amino-2-methyl-1-propanol, and 2-(2-aminoethoxy)ethanol. Polyether diamines having oxygen in the skeleton can also be used. The polyether has the general formula H2N-R 1 -(RO) n -R 2 -NH2 (wherein n is 2 to 100; R 1 , R 2is an alkyl group or an alicyclic hydrocarbon group having 1 to 14 carbon atoms, and R is an alkyl group or an alicyclic hydrocarbon group having 1 to 10 carbon atoms. The alkyl group may be linear or branched.) Examples of this ether diamine include polyoxypropylene diamine, and commercially available products include Jeffamines (manufactured by Sun Techno Chemical Co., Ltd.). Bis-(3-aminopropyl)-polytetrahydrofuran can also be used. The polyamines and dimer acids or various dicarboxylic acids are thermally condensed by a conventional method, and various polyamide resins including dimer acid modified polyamide resins are produced by an amidation process accompanied by dehydration. In general, the reaction temperature is about 100 to 300°C, and the reaction time is about 1 to 8 hours.

[0062] [Polyester resin] The polyester resin is a polymer composed of polyvalent carboxylic acid and polyhydric alcohol as monomers. Known polyester resins can be used, and specifically, from the viewpoint of ensuring the cohesive force of the resin, it is preferable that the weight average molecular weight is 1,000 to 100,000. In addition, from the viewpoint of adhesion, it is preferable that the glass transition temperature is -10°C to 200°C. Examples of the polyvalent carboxylic acid component include aromatic dicarboxylic acids, aliphatic dicarboxylic acids, unsaturated dicarboxylic acids, trivalent or higher carboxylic acids, etc., from which one or more can be selected and used, while examples of the polyhydric alcohol component include aliphatic glycols, ether glycols, trivalent or higher polyalcohols, etc., from which one or more can be selected and used. Commercially available polyester resins include Vylon (manufactured by Toyobo Co., Ltd., "Vylon" is a registered trademark), Polyester (manufactured by Nippon Synthetic Chemical Industry Co., Ltd., "Polyester" is a registered trademark), and Teslac (manufactured by Hitachi Chemical Polymer Co., Ltd., "Teslac" is a registered trademark).

[0063] From the viewpoints of fluidity during heating, volume resistivity, adhesion to a substrate, and durability, it is also preferable for the binder resin to contain a vinyl polymer having at least one structure selected from the group consisting of polyether, polyester, polycarbonate, and polybutadiene, which has a functional group capable of reacting with an isocyanate group, in a side chain. The method of introducing the side chain is not particularly limited, and it can be obtained by various synthesis methods.

[0064] Examples of functional groups capable of reacting with an isocyanate group include a hydroxyl group, an amino group, a carboxyl group, an epoxy group, an N-methylol group, and an N-alkoxymethyl group, with a hydroxyl group being preferred in terms of reactivity. The functional group capable of reacting with an isocyanate group can be introduced into the side chain or main chain of the vinyl polymer, and the method of introduction is not particularly limited and can be introduced by various synthesis methods. When used in applications requiring high toughness and durability, it is desirable to directly introduce a functional group capable of reacting with an isocyanate into the main chain of the vinyl polymer, which can improve the crosslink density of the resin.

[0065] The weight average molecular weight of the vinyl polymer in terms of polystyrene is preferably 5,000 to 500,000, and more preferably 10,000 to 100,000. When the weight average molecular weight is 500,000 or less, the solubility in a solvent is improved, and when it is 5,000 or more, sufficient coating strength is obtained after (hot) pressing.

[0066] The binder resin may be a curable resin that undergoes a curing (crosslinking) reaction after the binder resin is applied to a substrate. The crosslinking agent used in the curable resin is not particularly limited, but may be a polyisocyanate compound having two or more isocyanate groups, etc. The polyisocyanate compound is not particularly limited, but when used outdoors, it is preferable to use only alicyclic or aliphatic compounds in order to prevent the coating film from deteriorating over time. Examples of the alicyclic polyisocyanate compound include isophorone diisocyanate, hydrogenated tolylene diisocyanate, and hydrogenated 4,4'-diphenylmethane diisocyanate. Examples of the aliphatic polyisocyanate compound include trimethylhexamethylene diisocyanate, 4,4'-diphenylmethane diisocyanate, hexamethylene diisocyanate, and lysine diisocyanate. Examples of aromatic polyisocyanate compounds include diphenylmethane diisocyanate, toluylene diisocyanate, naphthylene-1,5-diisocyanate, o-xylene diisocyanate, m-xylene diisocyanate, p-xylene diisocyanate, triphenylmethane triisocyanate, and polymethylene polyphenylisocyanate. As the polyisocyanate compound, an adduct having isocyanates at both ends of the above-mentioned compound and a glycol or a diamine, a biuret modified compound, or an isocyanurate modified compound may be used. In particular, when the polyisocyanate compound contains an isocyanurate modified product, particularly an isocyanurate ring-containing triisocyanate, sufficient coating strength can be obtained after heat pressing, which is preferable. Specific examples of the isocyanurate ring-containing triisocyanate include isocyanurate-modified isophorone diisocyanate (e.g., Desmodur Z4470 manufactured by Sumitomo Bayer Urethane Co., Ltd.), isocyanurate-modified hexamethylene diisocyanate (e.g., Sumidur N3300 manufactured by Sumitomo Bayer Urethane Co., Ltd.), and isocyanurate-modified toluylene diisocyanate (e.g., Sumidur FL-2, FL-3, FL-4, HLBA manufactured by Sumitomo Bayer Urethane Co., Ltd.). The polyisocyanate compounds may be used alone or in combination of two or more kinds, depending on the required performance, in such a ratio that the total number of isocyanate groups is preferably 0.1 to 5.0 times, more preferably 0.5 to 3.0 times, and particularly preferably 0.8 to 2.0 times, relative to the total number of functional groups of the binder resin.

[0067] The binder resin may be in the form of either a soluble resin that dissolves in a solvent, or a dispersion-type resin fine particle (emulsion) that does not dissolve in a solvent and exists in the form of fine particles.

[0068] The particle structure of the dispersion type resin fine particles can be a multi-layer structure, so-called core-shell particles. For example, by localizing a resin obtained by mainly polymerizing a monomer having a functional group in the core or shell, or by providing a difference in Tg or composition between the core and the shell, it is possible to improve the curability, drying property, film-forming property, and mechanical strength of the binder. From the viewpoint of binding property and particle stability, the average particle size of the resin fine particles is preferably 10 to 1000 nm, and more preferably 10 to 300 nm. In addition, since the stability of the particles is impaired when a large amount of coarse particles exceeding 1 μm are contained, it is preferable that the amount of coarse particles exceeding 1 μm is at most 5% or less. The above-mentioned average particle size refers to the volume average particle size, and can be measured by dynamic light scattering. Measurement of the average particle size by dynamic light scattering can be performed as follows. Depending on the solid content of the resin fine particles, they are diluted 200 to 1000 times with the same dispersion liquid as the dispersion medium. About 5 ml of the diluted dispersion liquid is poured into the cell of a measuring device (Nanotrack manufactured by Nikkiso Co., Ltd.), and the dispersion medium and resin refractive index conditions according to the sample are input, and then measurement is performed. The volume particle size distribution data (histogram) obtained at this time can be used to measure the average particle size. The dispersed resin particles preferably contain crosslinked resin particles. The crosslinked resin particles refer to resin particles having an internal crosslinked structure (three-dimensional crosslinked structure), and it is important that the particles are crosslinked inside. In addition, the crosslinked resin particles contain specific functional groups, which can contribute to adhesion to the substrate. Furthermore, by adjusting the amount of the crosslinked structure and functional groups, a coating film with excellent durability can be obtained.

[0069] From the viewpoint of environmental load, etc., a water-soluble resin and aqueous resin fine particles that can be used in an aqueous solvent, preferably in water, are preferred. Also, from the viewpoint of the slurry stability and coatability of the conductive composition, it is more preferred to use a water-soluble resin and aqueous resin fine particles in combination.

[0070] [Water-soluble resin] A water-soluble resin is a resin that can be completely dissolved in water without separation or precipitation after 1 g of the resin is added to 99 g of water at 25° C., stirred, and left for 24 hours at 25° C. Water-soluble resins have the effect of increasing the dispersibility of carbon materials, so a stable composition can be obtained with a small amount of resin. Water-soluble resins are roughly classified into anionic resins, cationic resins, amphoteric resins having both anionic and cationic properties, and other nonionic resins, and further, the resins may be composed of a plurality of monomers. Moreover, the water-soluble resins may be used alone or in combination of two or more kinds. Examples of anionic resins include resins containing a skeleton containing a carboxyl group, a sulfo group, a phosphoric acid group, or a partially or completely neutralized skeleton thereof. Examples of such resins include homopolymers of polymerizable monomers such as (meth)acrylic acid, itaconic acid, fumaric acid, maleic acid, 2-sulfoethyl methacrylate, and 2-methacryloyloxyethyl acid phosphate, copolymers thereof with other polymerizable monomers, carboxymethyl cellulose, and alkali neutralized products thereof. Examples of cationic resins include resins containing a cyclic amino group, a skeleton in which the amino group is partially or completely neutralized, and quaternary ammonium salts. Examples of the resins include homopolymers of polymerizable monomers such as N,N-dimethylaminoethyl (meth)acrylate, N,N-diethyl (meth)acrylate, and vinylpyridine, copolymers with other polymerizable monomers, and acid-neutralized products thereof. Examples of amphoteric resins include resins containing both the anionic skeleton and the cationic skeleton, such as copolymers of styrene, maleic acid, and N,N-dimethylaminoethyl (meth)acrylate. The nonionic resin is a resin other than the anionic, cationic and amphoteric resins. Examples of the nonionic resin include polyvinylpyrrolidone, polyvinyl alcohol, polyvinyl butyral, polyacrylamide, poly-N-vinylacetamide, and polyalkylene glycol. The molecular weight of the water-soluble resin is not particularly limited, but the mass average molecular weight is preferably 5,000 to 2,500,000. The mass average molecular weight (Mw) refers to the molecular weight calculated as polyethylene oxide by gel permeation chromatography (GPC).

[0071] [Aqueous resin fine particles] Aqueous resin microparticles (aqueous emulsions) are dispersion-type resin microparticles in which the resin does not dissolve in water and exists in the form of fine particles, and examples of such microparticles include (meth)acrylic emulsions, nitrile emulsions, urethane emulsions, polyolefin emulsions, fluorine-based emulsions (polyvinylidene fluoride (PVDF) and polytetrafluoroethylene (PTFE)), and diene emulsions (styrene-butadiene rubber (SBR)). Note that (meth)acrylic means either methacrylic or acrylic. When a coating film is formed from a conductive composition containing aqueous resin microparticles, the composition has excellent adhesion between particles and to a substrate, and can provide a coating film with high strength. Furthermore, because of the excellent adhesion, only a small amount of aqueous resin microparticles is required, and as a result, the conductivity of the conductive composition is improved. In order to obtain the above-mentioned effects, the aqueous resin microparticles are preferably (meth)acrylic emulsions or urethane emulsions, which have excellent interparticle adhesion and flexibility (film flexibility).

[0072] The (meth)acrylic emulsion is an emulsion polymer containing 10 parts by mass or more of a monomer having a (meth)acryloyl group, preferably 20 parts by mass or more, more preferably 30 parts by mass or more. The monomer having an acryloyl group has excellent reactivity, so that resin microparticles can be relatively easily produced. Therefore, the (meth)acrylic emulsion is particularly preferable as the aqueous resin microparticle.

[0073] <Solvent> In the conductive composition of the present invention, a solvent can be appropriately used when dispersing the carbon material or when uniformly mixing the carbon material and the binder resin. Such a solvent is not particularly limited as long as it can dissolve the resin or can stably disperse the resin fine particle emulsion, and examples of such a solvent include water and organic solvents.

[0074] The organic solvent can be appropriately selected from among alcohols such as methanol, ethanol, propanol, butanol, ethylene glycol methyl ether, and diethylene glycol methyl ether; ketones such as acetone, methyl ethyl ketone, methyl isobutyl ketone, and cyclohexanone; ethers such as tetrahydrofuran, dioxane, ethylene glycol dimethyl ether, and diethylene glycol dimethyl ether; hydrocarbons such as hexane, heptane, and octane; aromatics such as benzene, toluene, xylene, and cumene; and esters such as ethyl acetate and butyl acetate, depending on the composition of the conductive composition. The solvent may be a combination of water and an organic solvent, or a combination of two or more organic solvents.

[0075] When using a water-soluble resin or aqueous resin particles, it is preferable to use water as a solvent from the viewpoint of solubility and dispersibility, and a liquid medium compatible with water may be added as necessary. As the liquid medium compatible with water, an alcohol-based solvent having a carbon number of 4 or less is preferable. In addition, various additives such as ultraviolet absorbers, ultraviolet stabilizers, radical scavengers, fillers, thixotropy-imparting agents, antiaging agents, antioxidants, antistatic agents, flame retardants, thermal conductivity improvers, plasticizers, anti-sagging agents, antifouling agents, preservatives, bactericides, defoamers, leveling agents, antiblocking agents, curing agents, thickeners, dispersants, and silane coupling agents may be added to the resin composition of the present invention, if necessary, within a range that does not impair the effects of the present invention.

[0076] <Two or more different carbon materials> As described above, the conductive composition of the present invention can contain two or more different carbon materials selected from the carbon materials of the present invention. The combination of two or more different carbon materials is not particularly limited, but is preferably a combination of two or more carbon materials having different specific surface areas; a combination of two or more carbon materials having different types of carbon, such as graphite and graphite, graphite and carbon nanotubes, or graphite and graphene (graphene nanoplatelets); or a combination thereof. When two or more carbon materials having different specific surface areas are used in combination, the specific surface area of ​​the carbon material having the largest specific surface area is preferably 5 to 1500 m 2 / g.

[0077] The conductive film formed from the conductive composition containing two or more different carbon materials of the present invention is a uniform conductive film with high packing between the carbon materials and high density, so it is presumed that the conductive network between the carbon materials in the film and the durability of the conductive film are improved. Furthermore, it is presumed that the wettability is improved by using two or more carbon materials in combination, the interaction with the binder resin is changed, and the binder resin is less likely to cover the carbon material surface, making it difficult for the binder resin to exist at the contact points between the carbon materials, and the contact resistance of the carbon material is reduced. Furthermore, when two or more carbon materials are used in combination, the viscosity tends to decrease due to the improvement of dispersibility, and the effect of making the dispersion easier to handle is observed, and further the coatability is improved. It is presumed that due to these effects, by using two or more different carbon materials, a conductive film with extremely excellent conductivity can be formed.

[0078] <Conductive assistant> The conductive composition of the present invention may further contain a conductive assistant other than the carbon material of the present invention, if necessary. The conductive assistant may be any one that does not fall under the specific boron-containing carbon material of the present invention, and examples thereof include carbon assistants such as carbon black, activated carbon, graphite, conductive carbon fibers (carbon nanotubes, carbon nanofibers, etc.), carbon nanohorns, graphene, graphene nanoplatelets, and nanoporous carbon, and metal assistants such as metal nanoparticles (silver, copper, etc.). The conductive assistant may contain boron or may be doped with boron. When the conductive assistant contains boron, the content of boron in the conductive assistant is preferably 0.01 to 2 mol%, and more preferably 0.1 to 1.1 mol%. When the content of boron in the conductive assistant is 0.01 to 2 mol%, the wettability to the solvent or binder resin is increased, and the hardness of the conductive assistant is increased, thereby improving the dispersibility of the conductive composition and improving the durability against external forces such as impact, thereby improving the dispersion stability and film strength. From the viewpoint of specific surface area and particle size, the conductive assistant is preferably carbon black. Note that, as the carbon assistant, the carbon black, activated carbon, graphite, conductive carbon fiber (carbon nanotube, carbon nanofiber, etc.), carbon nanohorn, graphene, graphene nanoplatelet, and nanoporous carbon described above can be used.

[0079] The conductive assistant preferably has a larger specific surface area than the carbon material of the present invention, which is the conductive base material. The preferred specific surface area of ​​the conductive assistant is 5 to 1500 m 2 / g, more preferably 20 to 1300m 2 / g, more preferably 110 to 900m 2 / g. The specific surface area of ​​the conductive additive is 1500 m 2 When the conductive composition has a specific surface area of ​​5 m / g or less, the conductive composition has good dispersibility and 2 When the content is 1 / g or more, gaps between the conductive base materials in the conductive film can be efficiently filled, and a conductive film having excellent conductivity and durability can be obtained. The specific surface area in the present invention refers to the specific surface area (BET) calculated from the amount of nitrogen adsorption.

[0080] The proportion of the boron-containing carbon material in the total solid content of the conductive composition is preferably 60 to 99 mass %, and more preferably 65 to 80 mass %. When the conductive composition further contains a conductive assistant, the proportion of the boron-containing carbon material in the total solid content of the conductive composition is preferably 40 to 85 mass%, more preferably 45 to 75 mass%, and even more preferably 50 to 60 mass%. On the other hand, the proportion of the conductive assistant in the total solid content of the conductive composition is preferably 5 to 20 mass%, more preferably 8 to 20 mass%, and further preferably 10 to 18 mass%. When the proportions of the carbon material and the conductive assistant in the total solid content of the conductive composition are 50 to 60 mass% and 10 to 18 mass%, respectively, the conductive composition has very good dispersibility, and a conductive film with particularly excellent conductivity and durability can be obtained.

[0081] The viscosity of the conductive composition can be appropriately adjusted depending on the coating method of the conductive composition, but is generally preferably 10 mPa·s or more and 30,000 mPa·s or less. The viscosity can be measured, for example, using a B-type viscometer. The viscosity of a dispersion containing a boron-containing carbon additive as a conductive additive tends to be lower than that of a dispersion prepared using a carbon additive that does not contain boron, due to the change in the surface state of the carbon additive as described above, and this has the effect of making the dispersion easier to handle.

[0082] (Dispersing machine / mixing machine) As an apparatus used in obtaining the conductive composition, a dispersing machine or a mixer that is generally used for dispersing pigments or the like can be used.

[0083] For example, mixers such as a Disper, Homomixer, or Planetary Mixer; homogenizers such as M-Technique's "Clearmix" or PRIMIX's "Filmix"; media-type dispersers such as a paint conditioner (Red Devil), ball mill, sand mill (Shinmaru Enterprises' "Dynomill", etc.), attritor, pearl mill (Eirich's "DCP Mill", etc.), or Coball mill; media-less dispersers such as wet jet mills (Zenus PY, Sugino Machine's "Starburst", Nanomizer, Nanomizer, etc.), M-Technique's "Clear SS-5", or Nara Machine's "MICROS"; or other roll mills, kneaders, ultrasonic dispersers, etc., may be mentioned, but are not limited to these.

[0084] For example, when using a media type disperser, it is preferable to use a method using a disperser whose agitator and vessel are made of ceramic or resin, or a disperser whose metallic agitator and vessel surface are treated with tungsten carbide spraying or resin coating, etc. As the media, it is preferable to use glass beads, or ceramic beads such as zirconia beads or alumina beads. Only one type of dispersing device may be used, or multiple types of devices may be used in combination.

[0085] <Conductive film> The conductive film of the present invention is a film formed from a conductive composition, and can be formed by applying the conductive composition onto a substrate and drying it as necessary.

[0086] (base material) The shape of the substrate used for forming the conductive film is not particularly limited and may be appropriately selected according to the application. The substrate is preferably in the form of a sheet, more preferably an insulating resin film.

[0087] The material of the substrate is not particularly limited, and examples thereof include PET (polyethylene terephthalate), PEN (polyethylene naphthalate), polyimide, polyvinyl chloride, polyamide, nylon, OPP (oriented polypropylene), and CPP (unoriented polypropylene).

[0088] As for the shape, a flat film is generally used, but substrates with a roughened surface, those treated with a primer, those with holes, and those in a mesh shape can also be used.

[0089] The method of applying the conductive composition on the substrate is not particularly limited, and any known method can be used. Examples of such application methods include die coating, dip coating, roll coating, doctor coating, knife coating, spray coating, gravure coating, screen printing, and electrostatic painting. Examples of drying methods include, but are not limited to, standing drying, blowing drying, hot air drying, infrared heating, and far infrared heating.

[0090] After coating, the conductive film may be rolled using a lithographic press or a calendar roll, and the rolling may be performed while heating in order to soften the conductive film and make it easier to press. The thickness of the conductive film is generally 0.1 μm or more and 1 mm or less, and preferably 1 μm or more and 200 μm or less.

[0091] (Volume resistivity of conductive film) The volume resistivity of the conductive film of the present invention is preferably 5×10 -3 Ω cm, preferably less than 2×10 -3 Ω cm, and more preferably less than 1×10 -3 The volume resistivity is less than 5×10 -3 With a resistivity of less than Ω·cm, this composition has extremely high conductivity and can be used for battery electrodes, current collectors, batteries, wiring in electronic devices, etc. EXAMPLES

[0092] The present invention will be described in more detail below with reference to examples, but the following examples are not intended to limit the scope of the invention. In the examples and comparative examples, "parts" refers to "parts by mass" and "%" refers to mass%.

[0093] <Production of boron-containing carbon materials> [Example 1] Boron-containing carbon material (1) Exfoliated graphite UP-20 (manufactured by Nippon Graphite Industries Co., Ltd.) and boric acid (manufactured by Fujifilm Wako Pure Chemical Industries, Ltd.) were weighed out to a mass ratio of 80 / 20 (exfoliated graphite / boric acid) and mixed in a mortar to obtain a mixture. The mixture was filled into a graphite crucible and heat-treated in a multipurpose high-temperature furnace under an argon atmosphere at 2200°C for 1 hour to obtain a boron-containing carbon material (1). It was cm.

[0094] [Example 2] Boron-containing carbon material (2) Spherical graphite CGB-50 (manufactured by Nippon Graphite Industries Co., Ltd.) and boric acid (manufactured by Fujifilm Wako Pure Chemical Industries, Ltd.) were weighed out to a mass ratio of 80 / 20 (spherical graphite / boric acid), and water was added as a solvent, mixed in a planetary centrifugal mixer, and dried in an oven at 80°C under atmospheric conditions to obtain a mixture. The mixture was filled into a graphite crucible and heat-treated in a multipurpose high-temperature furnace under an argon atmosphere at 2200°C for 1 hour to obtain a boron-containing carbon material (2).

[0095] [Example 3] Boron-containing carbon material (3) Spherical graphite CGB-50 (manufactured by Nippon Graphite Industries Co., Ltd.) and boric acid (manufactured by Fujifilm Wako Pure Chemical Industries, Ltd.) were weighed out to a mass ratio of 99 / 1 (spherical graphite / boric acid), and water was added as a solvent, mixed in a planetary centrifugal mixer, and dried in an oven at 80°C under atmospheric conditions to obtain a mixture. The mixture was filled into a graphite crucible and heat-treated in a multipurpose high-temperature furnace under an argon atmosphere at 2200°C for 1 hour to obtain a boron-containing carbon material (3).

[0096] [Comparative Example 1] Boron-containing carbon material (4) Spherical graphite CGB-50 (manufactured by Nippon Graphite Co., Ltd.) and boric acid (manufactured by Fujifilm Wako Pure Chemical Industries, Ltd.) were weighed out to a mass ratio of 80 / 20 (spherical graphite / boric acid), and water was added as a solvent, mixed in a planetary centrifugal mixer, and dried in an oven at 80°C under atmospheric conditions to obtain a mixture. The mixture was filled into a graphite crucible and heat-treated in a multipurpose high-temperature furnace under an argon atmosphere at 1000°C for 1 hour to obtain a boron-containing carbon material (4).

[0097] [Comparative Example 2] Boron-containing carbon material (5) Multi-walled carbon nanotubes (MWCNT) NTP3003 (NTP) and boric acid (Fujifilm Wako Pure Chemical Industries, Ltd.) were weighed out to a mass ratio of 80 / 20 (MWCNT / boric acid) and mixed in a mortar to obtain a mixture. The mixture was filled into a graphite crucible and heat-treated in a multi-purpose high-temperature furnace under an argon atmosphere at 2000°C for 1 hour to obtain a boron-containing carbon material (5).

[0098] [Comparative Example 3] Boron-containing carbon material (6) Graphene nanoplatelets (GNP) xGnP-C-750 (manufactured by XG Sciences) and boron carbide (manufactured by Fujifilm Wako Pure Chemical Industries, Ltd.) were weighed out to a mass ratio of 96 / 4 (GNP / boron carbide) and mixed in a mortar to obtain a mixture. The mixture was filled into a graphite crucible and heat-treated in a multipurpose high-temperature furnace under an argon atmosphere at 2800°C for 1 hour to obtain a boron-containing carbon material (6).

[0099] [Example 4] Boron-containing carbon material (7) 99 parts of expanded graphite GR-60 (manufactured by Nippon Graphite Industries Co., Ltd.), 1 part of boron carbide (manufactured by Fujifilm Wako Pure Chemical Industries Co., Ltd.), 300 parts of toluene as a solvent, and 100 parts of methanol were dispersed using a high shear mixer (L5M-A, manufactured by Silverson), and the solvent was dried to prepare a precursor. Next, the precursor was filled into a graphite crucible and heat-treated in a multipurpose high-temperature furnace under an argon atmosphere at 2200°C for 1 hour to obtain a boron-containing carbon material (7).

[0100] [Examples 5 to 12] Boron-containing carbon materials (8) to (15) Boron-containing carbon materials (8) to (15) were obtained in the same manner as for the boron-containing carbon material (7), except that the raw materials and heating temperature conditions shown in Table 2 were used.

[0101] <Evaluation of boron-containing carbon materials> The physical properties of the prepared boron-containing carbon materials were evaluated by the following methods. The results are shown in Tables 1 and 2.

[0102] [G / D ratio] The G / D ratio was evaluated using a laser Raman spectrophotometer NRS-3100 manufactured by JASCO Corporation. The measurements were performed under conditions of an excitation laser wavelength of 532 nm, and the D band (1330 to 1370 cm) of the Raman spectrum of each sample was measured. -1 ) and G band (1560~1620cm -1 The G / D ratio was calculated from the peak intensity ratio (IG / ID).

[0103] [Ratio of surface-substitutional boron to all elements on the surface of boron-containing carbon material] The ratio of the total surface boron element and the ratio of the surface substitutional boron element were determined using an X-ray photoelectron spectrometer K-Alpha manufactured by ThermoFisher Scientific. In detail, the ratio B of the total surface boron element was calculated from the total spectrum area obtained from the boron B1s spectrum peak. In addition, the ratio BR of the surface substitutional boron element was calculated from the ratio of the peak area of ​​188 to 189.3 eV to the total spectrum area of ​​boron, and the ratio of the surface substitutional boron element to the total elements on the surface of the boron-containing carbon material was calculated by B×BR. In addition, in the carbon material of Comparative Example 1, no spectrum was confirmed in the region of 188 to 189.3 eV in the B1s spectrum, and therefore surface-substitutional boron element could not be detected.

[0104] [Crystallite size (La)] An X-ray diffractometer (Rigaku Corporation, Smartlab) was used for measurement with CuKα radiation as the X-ray source, and the crystallite size (La) was calculated from the peak position and half-width of the (110) plane derived from the graphite skeleton near 2θ = 77.0 to 78.5°.

[0105] [Volume resistivity] The volume resistivity was evaluated using a powder resistivity measurement system MCP-PD51 manufactured by Mitsubishi Chemical Analytech Co., Ltd. Measurements were performed using a four-point probe method with a low-resistance powder probe, and the volume resistivity value was used when a load of 20 kN was applied to each sample.

[0106] [Table 1]

[0107] [Table 2]

[0108] According to Tables 1 and 2, the volume resistivity of all the boron-containing carbon materials of the examples was significantly lower than that of the comparative examples, and a lower resistance was confirmed. This is believed to be due to the improvement of electronic conductivity by achieving both carrier doping by substitutional boron and maintaining mobility by a high G / D ratio. Thus, the boron-containing carbon material having a G / D ratio and a substitutional boron element amount within the range of the present invention exhibited a significantly high electrical conductivity.

[0109] It was also found that the difference in the G / D ratio of the boron-containing carbon material has a significant effect on the electrical conductivity. Comparing the results of Examples 4-7 with different G / D ratios, carbon materials (9) and (10) with G / D ratios in the range of 2.0 to 5.0 showed significantly excellent electrical conductivity. It was also found that the difference in the crystallite size (La) of the boron-containing carbon material has a significant effect on the electrical conductivity. Comparing the results of Examples 6 and 8-12, which have different crystallite sizes (La), carbon materials (9), (11), (12) and (15), which have La in the range of 30 to 70 nm, showed significantly excellent electrical conductivity.

[0110] <Production of binder resin> [Production Example 1] Polyurethane resin solution A reaction vessel equipped with a stirrer, thermometer, reflux condenser, dropping device, and nitrogen inlet tube was charged with 455.5 parts of a polyester polyol obtained from terephthalic acid, adipic acid, and 3-methyl-1,5-pentanediol ("Kuraray Polyol P-2011" manufactured by Kuraray Co., Ltd., Mn=2,011), 16.5 parts of dimethylolbutanoic acid, 105.2 parts of isophorone diisocyanate, and 140 parts of toluene, and reacted at 90°C for 3 hours under a nitrogen atmosphere, and 360 parts of toluene was added to this to obtain a urethane prepolymer solution having isocyanate groups. Next, 969.5 parts of the obtained urethane prepolymer solution having isocyanate groups was added to a mixture of 19.9 parts of isophorone diamine, 0.63 parts of di-n-butylamine, 294.5 parts of 2-propanol, and 335.5 parts of toluene (the total equivalent of amino groups relative to the free isocyanate groups at both ends of the urethane prepolymer was 0.98), and the mixture was reacted at 50°C for 3 hours, followed by reaction at 70°C for 2 hours. The mixture was then diluted with 126 parts of toluene and 54 parts of 2-propanol to obtain a polyurethane resin solution having a weight average molecular weight of 61,000 and an acid value of 10 mgKOH / g. The obtained polyurethane resin solution was diluted with toluene / methyl ethyl ketone / 2-propanol (mass ratio: 1 / 1 / 1) to obtain a polyurethane resin solution with a solid content of 20 mass %.

[0111] [Production Example 2] Polyamide resin solution In a four-neck flask equipped with a stirrer, a reflux condenser, a nitrogen inlet tube, an inlet tube, and a thermometer, 156.2 parts of Pripol 1009 (hydrogenated dimer acid, Croda Japan Co., Ltd.) as a polybasic acid compound, 5.5 parts of 5-hydroxyisophthalic acid, 146.4 parts of Priamine 1074 (Croda Japan Co., Ltd.) as a polyamine compound, and 100 parts of ion-exchanged water were charged and stirred until the temperature of the heat generation became constant. When the temperature stabilized, the temperature was raised to 110°C, and after confirming the outflow of water, the temperature was raised to 120°C after 30 minutes, and then the dehydration reaction was continued while raising the temperature by 10°C every 30 minutes. After the temperature reached 230°C, the reaction was continued at that temperature for 3 hours, and the temperature was lowered by holding it under a vacuum of about 2 kPa for 1 hour. Finally, an antioxidant was added to obtain a polyamide resin having a weight average molecular weight of 24,000, an acid value of 13.2 mgKOH / g, a hydroxyl value of 5.5 mgKOH / g, and a glass transition temperature of -32°C. The obtained polyamide resin was diluted with toluene / 2-propanol (mass ratio: 2 / 1) to obtain a polyamide resin solution with a solid content of 20 mass %.

[0112] [Production Example 3] Polyester resin solution Vylon 200 (polyester resin, manufactured by Toyobo Co., Ltd.) was diluted with toluene / methyl ethyl ketone (mass ratio: 1 / 1) to obtain a polyester resin solution with a solid content of 20 mass %.

[0113] The resins were evaluated as follows. (Weight average molecular weight (Mw)) The weight average molecular weight was measured using a gel permeation chromatography (GPC) "HPC-8020" manufactured by Tosoh Corporation. GPC is a liquid chromatography that separates and quantifies substances dissolved in a solvent (THF; tetrahydrofuran) based on the difference in their molecular size. The measurement in the present invention was performed using two "LF-604" columns (manufactured by Showa Denko K.K.: GPC column for rapid analysis: 6 mm ID x 150 mm size) connected in series, at a flow rate of 0.6 ml / min and a column temperature of 40°C, and the weight average molecular weight was determined in polystyrene equivalent.

[0114] (Acid Value (AV)) Approximately 1 g of sample was precisely weighed and placed in a stoppered Erlenmeyer flask, and 100 ml of a toluene / ethanol (volume ratio: toluene / ethanol = 2 / 1) mixture was added to dissolve it. Phenolphthalein test solution was added as an indicator and the mixture was allowed to stand for 30 seconds. After that, the solution was titrated with 0.1 N alcoholic potassium hydroxide solution until it turned a light pink color, and the acid value was calculated using the following formula. Acid value (mgKOH / g) = (5.611 x a x F) / S, where S: Amount of sample collected (g) a: Consumption of 0.1N alcoholic potassium hydroxide solution (ml) F: Potency of 0.1N alcoholic potassium hydroxide solution

[0115] (Hydroxyl Value (OHV)) The hydroxyl value is the amount of hydroxyl groups contained in 1 g of the hydroxyl-containing resin, expressed as the amount (mg) of potassium hydroxide required to neutralize the acetic acid bonded to the hydroxyl groups when the hydroxyl groups are acetylated. The hydroxyl value was measured according to JIS K0070, and in the present invention, it was calculated taking into account the acid value as shown in the following formula. Approximately 1 g of sample was precisely weighed and placed in a stoppered Erlenmeyer flask, and 100 ml of a toluene / ethanol (volume ratio: toluene / ethanol = 2 / 1) mixture was added and dissolved. Exactly 5 ml of an acetylating agent (a solution of 25 g of acetic anhydride dissolved in pyridine to a volume of 100 ml) was then added and stirred for approximately 1 hour. Phenolphthalein test solution was added as an indicator and allowed to stand for 30 seconds. After that, the solution was titrated with 0.1 N alcoholic potassium hydroxide solution until it turned a light pink color, and the hydroxyl value was calculated using the following formula. Hydroxyl value (mgKOH / g) = [{(ba) × F × 28.05} / S] + D however, S: Amount of sample collected (g) a: Consumption of 0.1N alcoholic potassium hydroxide solution (ml) b: Amount of 0.1N alcoholic potassium hydroxide solution consumed in the blank experiment (ml) F: Potency of 0.1N alcoholic potassium hydroxide solution D: Acid value (mgKOH / g)

[0116] (Glass transition temperature (Tg)) The glass transition temperature of the resin was measured by drying and removing the solvent from the resin and heating it from -80 to 150°C at a rate of 2°C / min using a Mettler Toledo DSC-1.

[0117] <Production of conductive additives> [Manufacturing example 4] CB(4) 93 parts of EC-600J (Ketjen Black, Lion Specialty Chemicals) and 7 parts of boric acid (Fujifilm Wako Pure Chemical Industries, Ltd.) were mixed with 800 parts of toluene and 100 parts of ethanol as solvents, mixed in a planetary centrifugal mixer, and dried in an oven at 80°C under atmospheric conditions to obtain a mixture. The mixture was filled into a graphite crucible and heat-treated in a multipurpose high-temperature furnace under an argon atmosphere at 1700°C for 1 hour to obtain CB(4). The G / D ratio of CB(4) was 0.75, and the boron content was 1.03 mass%. The boron content was measured in the carbon material using ICP emission spectroscopy (SPECTROARCOS FHS12 manufactured by SPECTRO).

[0118] [Manufacturing example 5] CB(5) Except for using 88 parts of EC-600J and 12 parts of boric acid, CB(5) was obtained in the same manner as in Production Example 4. The G / D ratio of CB(5) was 0.71, and the boron content was 1.81% by mass.

[0119] [Production example 6] CB(6) Except for using 86.5 parts of EC-600J and 13.5 parts of boric acid, CB(6) was obtained in the same manner as in Production Example 4. The G / D ratio of CB(6) was 0.66, and the boron content was 2.02% by mass.

[0120] <Production of conductive compositions and conductive films> [Example A1] 85 parts of carbon material (7), 75 parts of polyester resin solution (15 parts of resin solids) as binder resin, and 170 parts of toluene / methyl ethyl ketone / 2-propanol (mass ratio: 1 / 1 / 1) as solvent were mixed in a mixer, and further dispersed in a sand mill to obtain a conductive composition (1). Next, this conductive composition (1) was applied onto a PET film substrate having a thickness of 100 μm using a doctor blade, and then dried in an oven. Then, roll pressing was performed under a linear pressure of 300 kg / cm to obtain a conductive film (1).

[0121] [Examples A2 to A4, Comparative Examples A1 to A3] Conductive compositions (2) to (7) and conductive films (2) to (7) were obtained in the same manner as in Example A1, except that the blending composition was changed to that shown in Table 3.

[0122] [Example A5] 61 parts of carbon material (13), 9 parts of CB (1) as a conductive assistant, 150 parts of polyamide resin solution (resin solid content 30 parts) as a binder resin, and toluene / methyl ethyl ketone / 2-propanol (mass ratio: 1 / 1 / 1) as a solvent were mixed in a mixer so that the solid content in the composition was 30 mass%, and further dispersed in a sand mill to obtain a conductive composition (8). Next, this conductive composition (8) was applied to a PET film substrate with a thickness of 100 μm using a doctor blade, and then dried in an oven to obtain a conductive film (8).

[0123] [Examples A6 to A23, Comparative Examples A4 to A6] Conductive compositions (9) to (26), (30) to (32) and conductive films (9) to (26), (30) to (32) were obtained in the same manner as in Example A5, except that the blending compositions were changed to those shown in Table 3.

[0124] [Example A24] 57 parts of the carbon material (10), 18 parts of CB (2) (acetylene black HS-100, manufactured by Denka Co., Ltd.) as a conductive assistant, and 250 parts of an aqueous solution (resin solid content: 5 parts) in which 2% by mass of water-soluble resin CMC (carboxymethylcellulose #1240, manufactured by Daicel Miraize Co., Ltd.) as a binder resin was dissolved were mixed in a mixer and further dispersed in a sand mill. Next, 40 parts (resin solid content 20 parts) of aqueous resin fine particles (Polyacrylic emulsion W-168, manufactured by Toyochem Co., Ltd., solid content 50 mass %) as a binder resin were added and mixed with a mixer to obtain a conductive composition (27). Next, this conductive composition (27) was applied onto a PET film substrate having a thickness of 100 μm using a doctor blade, and then dried in an oven to obtain a conductive film (27).

[0125] [Examples A25 and A26] Conductive compositions (28) and (29) and conductive films (28) and (29) were obtained in the same manner as in Example A24, except that the blending compositions were changed to those shown in Table 3.

[0126] <Evaluation of conductive compositions and conductive films> The obtained conductive compositions and conductive films were evaluated by the following methods. The evaluation results are shown in Table 3.

[0127] [Dispersion stability evaluation] The dispersion stability was evaluated based on the change in the liquid properties after the conductive composition was left to stand for 7 days at 25° C. The change in the liquid properties was judged based on the ease of stirring when stirred with a spatula. Judgment criteria ○: No change in liquid properties (good) △: Viscosity has increased, but gelation has not occurred (passable) ×: Gelled (bad)

[0128] [Coatability evaluation] The obtained conductive film was observed at 500 times magnification using a video microscope VHX-900 (manufactured by Keyence Corporation), and coating unevenness and pinholes were judged according to the following criteria. Coating unevenness was judged based on the shading of the film surface. Pinholes were judged based on the presence or absence of uncoated defects in the film. <<Uneven coating>> ○: No shading on the film surface is observed (good) △: There are 2 to 3 areas of shading on the film surface, but these are very small areas (OK) ×: Many shading patterns are observed on the film surface, or one or more shading stripes with a length of 5 mm or more are observed (defective). "Pinhole" ○: No pinholes found (good) △: There are 2 to 3 pinholes, but they are extremely small (passable) ×: Many pinholes are found, or one or more pinholes with a diameter of 1 mm or more are found (defective).

[0129] [Volume resistivity of film] The volume resistivity of the conductive film was measured by a four-terminal method using Loresta GP (manufactured by Nitto Seiko Analytech Co., Ltd.) in accordance with JIS-K7194.

[0130] [Film durability] The durability of the conductive film was evaluated by scratch hardness (pencil method) using an HB pencil in accordance with JIS K5600-5-4:1999. ○: No plastic deformation or cohesive failure occurs (good) △: Plastic deformation or cohesive failure has partially occurred (OK) ×: Plastic deformation and cohesive failure occurred (bad)

[0131] [Table 3]

[0132] According to the results in Table 3, the conductive composition using the boron-containing carbon material of the present invention has excellent dispersion stability and coatability, and the conductive film formed from the conductive composition has both high conductivity and durability. Moreover, by comparing Examples A1 to A4, it was found that the difference in the G / D ratio of the carbon material significantly affects the properties of the conductive composition and the conductive film. Furthermore, a comparison of Examples A14 to A19 revealed that differences in the crystallite size (La) of the carbon material, and a comparison of Examples A24 to A26 revealed that differences in the proportion of surface-substitutional boron element in the carbon material, significantly affected the properties of the conductive composition and conductive film. On the other hand, when focusing on the conductive assistant, a comparison of Examples A5, A6, A9, and A11 revealed that the dispersion stability and coatability of the conductive composition and the properties of the conductive film differ depending on the composition ratio of the conductive assistant in the conductive composition. Moreover, by comparing Examples A20 to A23, it was found that the boron content of the conductive assistant also affects the coatability of the conductive composition and the properties of the conductive film. Therefore, these results suggest that factors other than the conductivity caused by the carbon material are involved. Although the details are unclear at this stage, the conductive composition of the present invention is presumed to exhibit excellent conductivity by efficiently forming a conductive network of the carbon material in the film, since the boron-containing carbon material itself not only has excellent conductivity, but also has good dispersibility and dispersion stability, and further has good coatability. It is also presumed that the uniform network of the carbon material also leads to improved durability of the conductive film. In addition, the boron-containing carbon material of the present invention not only has improved wettability with respect to solvents and binder resins, but also tends to have a higher hardness, which is thought to affect dispersibility and coatability. It is considered that this is why the conductive composition containing the boron-containing carbon material has improved dispersibility and coatability and exhibits excellent conductivity.

Claims

1. A boron-containing carbon material doped with boron to substitute for at least a portion of the carbon elements in a carbon skeleton, A conductive composition comprising a boron-containing carbon material having an intensity ratio [G / D] of 1.0 or more between a G band and a D band in a laser Raman spectrum, and a ratio of surface-substituted boron elements to all elements on the surface of the boron-containing carbon material of 0.0001 or more as measured by X-ray photoelectron spectroscopy (XPS), and at least one of a binder resin and a solvent.

2. The conductive composition described in claim 1, wherein the boron-containing carbon material includes a graphite-based carbon material.

3. The conductive composition described in claim 1 or 2, wherein the boron-containing carbon material has an intensity ratio of G band to D band [G / D] of 1.25 to 5.

0.

4. The conductive composition described in any one of claims 1 to 3, wherein the boron-containing carbon material has a ratio of surface-substituted boron element of 0.0004 or more.

5. The conductive composition described in any one of claims 1 to 4, wherein the boron-containing carbon material has a crystallite diameter (La) of 28 to 80 nm.

6. The conductive composition according to any one of claims 1 to 5, further comprising a conductive assistant.

7. The conductive composition according to claim 6, wherein the proportion of the boron-containing carbon material in the total solid content of the conductive composition is in the range of 50 to 60 mass%, and the proportion of the conductive assistant is in the range of 10 to 18 mass%.

8. A conductive film formed from the conductive composition according to any one of claims 1 to 7.